A greater number of euploid blastocysts in a given cohort predicts excellent outcomes in single embryo transfer cycles - Morin, Scott (Springer US, 2014)
PURPOSE: This multicentered retrospective study analyzed whether the quantity of euploid blastocysts in a given cohort after comprehensive chromosomal screening can be used to identify candidates for single embryo transfer. METHODS: Blastocysts from 437 patients underwent trophectoderm biopsy followed by array comparative genomic hybridization. Embryos were then selected for single or double embryo transfer. The number of euploid blastocysts produced and transferred for each patient was recorded, as was clinical pregnancy rate and multiple gestation rate. RESULTS: In patients with ≤3 euploid blastocysts, clinical pregnancy rate was higher in double, compared to single embryo transfers. However, in patients with ≥4 euploid blastocysts, clinical pregnancy rate was not reduced with single embryo transfer was performed, whereas the multiple gestation rate was greatly reduced. CONCLUSIONS: Size of the euploid embryo cohort is a marker for success in single embryo transfer cycles. Patients who produce at least four euploid blastocysts are outstanding candidates for single embryo transer.